INSIDENSI DAN INTENSITAS BEBERAPA PENYAKIT UTAMA TANAMAN GAMBIR DI KABUPATEN LIMA PULUH KOTA - Putri, Diana; Waruwu, Arifda Ayu Swastini; Pradana, Ankardiansyah Pandu (Innofarm : Jurnal Inovasi Petanian, 2025)
Gambir is one of Indonesia’s superior commodities in the international market. However, problems that causes a decrease in the quality and productivity of gambir plants is disease attacks. The percentage and intensity of disease attacks on gambir plants in Lima Puluh Kota Regency have never been reported. This studi aimed termine the level of attack occurrence and intensity of diseases that attack gambir plants as basic information related to plant health status in an effort to manage diseases effectively. The study was conducted in three gambir land locations, using a survey method with Simple Random Sampling. Direct observation includes symptoms of attack, percentage and intensity of disease. The results of observations on land 1 and 2 found five main diseases namely red rust, brown spots, black spots, black mosaic and chlorosis, while on land 3 brown spot disease, dieback and black mosaic were found. The highest incidence of disease on land 1 was red rust which reached 100%, on land 2 red rust and brown spots were 100%, and on land 3 brown spot disease was 96%. The highest intensity of disease attack was red rust reaching 82% which was included in the category of very severe attacks. The high incidence and intensity of attacks of this disease are influenced by the age of the plants and the cultivation techniques used by gambir farmers, such as the lack of weed and disease control and fertilization. Keywords: Cultivation, disease intensity, gambir, red rust